Multi-omic approach to decipher the impact of skincare products with pre/postbiotics on skin microbiome and metabolome - Li, Min; Mao, Junhong; Diaz, Isabel; Kopylova, Evguenia; Melnik, Alexey V.; Aksenov, Alexander A.; Tipton, Craig D.; Soliman, Nadia; Morgan, Andrea M.; Boyd, Thomas (Frontiers in Medicine, 2023)
Introduction Although pre/pro/postbiotics have become more prevalent in dermatologic and cosmetic fields, the mode of action when topically applied is largely unknown. A multi-omic approach was applied to decipher the impact of the skincare products with pre/postbiotics on skin microbiome and metabolome. Methods Subjects with dry skin applied a body wash and body lotion with or without pre/postbiotics for 6 weeks. Skin hydration was measured at baseline, 3 and 6 weeks. Skin swabs were collected for 16S rRNA gene sequencing, metagenomics and metabolomics analysis. Results Skin hydration significantly increased in both groups. The prebiotic group significantly reduced opportunistic pathogens, e.g., Pseudomonas stutzeri and Sphingomonas anadarae, and increased the commensals, e.g., Staphylococcus equorum, Streptococcus mitis, Halomonas desiderata. Bacterial sugar degradation pathways were enriched in the prebiotic group, while fatty acid biosynthesis pathways were reduced in control. The changes on skin metabolome profiles by the products were more prominent. The prebiotic group performed greater modulation on many clinically-relevant metabolites compared to control. Correlation analysis showed H. desiderata and S. mitis positively correlated with skin hydration, P. stutzeri and S. anadarae negatively correlated with the metabolites that are positively associated with skin hydration improvement. Conclusion This holistic study supported a hypothesis that the pre/postbiotics increased skin hydration through the modulation of skin microbiome, metabolic pathways and metabolome.